2007
DOI: 10.1038/sj.npp.1301581
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Tryptophan Depletion on the Neural Correlates of Emotional Processing in Healthy Volunteers

Abstract: The processing of affective material is known to be modulated by serotonin (5-HT), but few studies have used neurophysiological measures to characterize the effect of changes in 5-HT on neural responses to emotional stimuli. We used functional magnetic resonance imaging to investigate the effect of acute tryptophan depletion, which reduces central 5-HT synthesis, on neural responses to emotionally valenced verbal stimuli. Though no participants experienced significant mood change, emotional information process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 55 publications
2
74
3
2
Order By: Relevance
“…These results fully concur with the above-mentioned SPECT study of Baeken et al (2010), which showed that increased 5-HT 2A receptor binding is related to the antidepressant effect of rTMS in depressed people. Importantly, in a recent study, tryptophan depletion also reduced the normal attentional bias toward positive stimuli in healthy people, which was accompanied by increased hemodynamic responses (f MRI) during the processing of emotional words in several subcortical structures (Roiser et al, 2008). In a review including 25 studies (Merens, Van der Does, & Spinhoven, 2007), serotonin manipulations were found to affect facial emotion recognition, attentional bias, emotional memory, dysfunctional attitudes, and decision making.…”
Section: Summary: An Integrative Frameworkmentioning
confidence: 99%
“…These results fully concur with the above-mentioned SPECT study of Baeken et al (2010), which showed that increased 5-HT 2A receptor binding is related to the antidepressant effect of rTMS in depressed people. Importantly, in a recent study, tryptophan depletion also reduced the normal attentional bias toward positive stimuli in healthy people, which was accompanied by increased hemodynamic responses (f MRI) during the processing of emotional words in several subcortical structures (Roiser et al, 2008). In a review including 25 studies (Merens, Van der Does, & Spinhoven, 2007), serotonin manipulations were found to affect facial emotion recognition, attentional bias, emotional memory, dysfunctional attitudes, and decision making.…”
Section: Summary: An Integrative Frameworkmentioning
confidence: 99%
“…Chronic antidepressant treatment facilitates exocytosis of 5-HT and/or increases its synaptic availability in corticolimbic regions extensively innervated by the DR, such as the prefrontal cortex, hippocampus, amygdala, and other forebrain structures implicated in mood regulation and stress adaptation (Steinbusch, 1981;Holmes, 2008). In contrast, 5-HT-depleting manipulations, such as through the 5-HT synthesis inhibitor, parachlorophenylalanine, or a diet deprived of the 5-HT precursor, tryptophan, precipitate anxiety and depression-like symptoms in animals (Blokland et al, 2002;Zhou et al, 2008;Roiser et al, 2008), exacerbate anxiogenic responses in human participants (Miller et al, 2000), and inflict a relapse in depressive patients (Smith et al, 1997). The delay in therapeutic onset of antidepressants has been attributed to gradual neuroplastic adaptations at the presynaptic and postsynaptic levels that result from the progressive augmentation in 5-HT activity.…”
Section: Introductionmentioning
confidence: 99%
“…Terdapat beberapa penelitian yang melaporkan hubungan linier efek kadar total triptofan plasma yang rendah dengan respon depresi, yaitu Wang dkk, 25 Roiser dkk, 26 Booij dkk, 27 dan Williams dkk. 28 Hasil berbeda dari penelitian Plasse 29 yang melaporkan efek kadar total triptofan plasma yang rendah (menurun 30%), belum memengaruhi kadar serotonin dan fungsi prefrontal cortex.…”
Section: Pembahasanunclassified